2018
DOI: 10.1038/nature25466
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of Bethe strings

Abstract: Almost a century ago, string states-complex bound states of magnetic excitations-were predicted to exist in one-dimensional quantum magnets. However, despite many theoretical studies, the experimental realization and identification of string states in a condensed-matter system have yet to be achieved. Here we use high-resolution terahertz spectroscopy to resolve string states in the antiferromagnetic Heisenberg-Ising chain SrCoVO in strong longitudinal magnetic fields. In the field-induced quantum-critical reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
85
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 41 publications
4
85
1
1
Order By: Relevance
“…Concomitantly, the continuum spectrum is replaced by a series of discrete spinon bound states. It has been found that the spinon confinement can be significantly tuned by applying a magnetic field [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concomitantly, the continuum spectrum is replaced by a series of discrete spinon bound states. It has been found that the spinon confinement can be significantly tuned by applying a magnetic field [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the weakly coupled quantum spin chain compound SrCo 2 V 2 O 8 has raised much attention due to the exotic magnetism that it hosts, including the magnetic-field-induced order-disorder transition [11], spinon confinement [5,12] and Bethe strings [7]. This compound crystallizes in a body-centred tetragonal lattice (space group I4 1 cd), in which 4-fold screw chains of CoO 6 -octahedra run along the crystallographic c-axis [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For attractive interactions with g < 0, there are also eigenstates in the form of one or several several stringsbound states of several particles, i.e., quantum solitons [24,25,44]. Although they remained a theoretical concept since they were introduced, very recently similar states-the Bethe strings-have been directly observed in an antiferromagnetic Heisenberg-Ising chain [45]. A superposition of strings with different velocities may remain localized for a finite time, so that it carries over into a MF multisoliton (breather) in the limit of N → ∞ [26][27][28].…”
mentioning
confidence: 99%